The Effect of Private Investment and Provincial Minimum Wage on Labor Absorption and Open Unemployment Rate in North Maluku Province - Rahman Senuk, Abdul (Journal of Social Science, 2024)
Unemployment is a labor problem that has now reached a fairly concerning condition. The problem of employment is undeniably one of the main problems faced in development. Wages are also the main factor that influences labor absorption. An increase in wage levels will increase the company's production costs which will ultimately lead to an increase in prices. The objectives of this study are: (1) To analyze the effect of private investment on labor absorption in North Maluku Province; (2) To analyze the effect of the provincial minimum wage (UMP) on labor absorption in North Maluku Province; (3) To analyze the effect of private investment on the open unemployment rate in North Maluku Province; (4) To analyze the effect of the Provincial Minimum Wage on the open unemployment rate in North Maluku Province; and (5) To analyze the effect of labor absorption on reducing the open unemployment rate in North Maluku Province. The analysis model used in this study is path analysis. The results of the study indicate that the provincial minimum wage (UMP) partially has a significant effect on labor absorption and the open unemployment rate in North Maluku Province. Meanwhile, private investment has an effect on employment opportunities but cannot reduce the unemployment rate. Then, opportunity has a significant influence and is negatively correlated with the open unemployment rate in North Maluku Province.